Added value from European Territorial Co-operation: the impact of demographic change in the Alps on the young - Marot, Naja; Gantar, Damjana; Černič Mali, Barbara (Bulletin of Geography. Socio-economic Series, 2015)
The article sets demographic change in the Alps in the framework of European Territorial Cooperation programs. A statistical overview of selected regions in five Alpine countries serves as a basis for further policy analysis. The latter was undertaken to reveal how transnational projects tackle youth issues, including the difficulties within the labour and real estate markets that appeared to be the most problematic factors influencing (out) migration of the youth. While there is only a minor recognition of the young in current policymaking on supranational, regional and local levels, the analysis showed that the added value of transnational programs for mountain regions and localities can be recognized in the development of multi-stakeholder environments, creating and transferring new solutions for the labour market as well as empowering youth participation in policy processes. However, the extent to which these solutions might contribute to overcoming the challenges of demographic change because of transnational programs is limited by various factors. Among these are the precise governance framework, administrative capacity, and population figures.